Strategi Pemberdayaan Ekonomi Desa Melalui Zakatnomics - Kikin Mutakin (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This Community Service (PkM) aims to provide education and guidance to the community about the urgency and strategy of economic empowerment in rural areas through the concept of zakatnomics. Village economic empowerment is needed in realizing the independence of rural communities through the concept of zakatnomics. Education and coaching in this PkM activity was carried out on August 13, 2022 in the Nasol Village Hall, Cikoneng District, Ciamis Regency. The implementation prioritizes collaboration with the Nasol Village Government which consists of the Village Consultative Body (BPD), the Village Zakat Collecting Unit (UPZ), the Village Indonesian Ulema Council (MUI) and cadres of Family Welfare Empowerment (PKK). The participants of this activity are representatives of small business actors in the Nasol Village area as many as 30 (thirty) people. The topic used as material in this activity is a discussion of how the rural economy can be empowered through the zakatnomics strategy. The potential for economic empowerment in Nasol Village needs encouragement both in terms of capital resources and human resources. One elaboration of the encouragement of capital resources can be applied through optimizing the role of the UPZ institution as an organization formed by the Regency National Amil Zakat Agency (BAZNAS) which is authorized to collect Zakat, Infaq and Alms (ZIS) funds and can be authorized in terms of assistance in the distribution of funds. The purpose of this PkM is to provide motivational stimulants and insight to the people of Nasol Village about economic empowerment strategies through integrated programs between Islamic financial practices, namely those sourced from ZIS funds and enthusiasm for economic activities. Keywords: Economic Empowerment, Zakatnomics, Islamic Finance, Village Independence.